Inhibition of sulphate reducing bacteria to enhance methane yield in anaerobic digester - Yaacob, Mohamad Syahrul Syazwan (2015)
Sulphate is a common constituent of industrial or domestic effluent and sometimes presents in high concentration. In anaerobic treatment, the reduction of sulphate to sulphide by sulphate reducing bacteria (SRB) leads to a number of problems. One of the major problems is low methane production. In order to retrieve successful anaerobic treatment of sulphate enriched wastewater, it is essential to control sulphate reduction in anaerobic digestion processes. Therefore, the aim of this research is to investigate the inhibition of SRB using ferric chloride (FeCl3) in an Upflow Anaerobic Sludge Blanket (UASB) reactor treating sulphate enriched wastewater. The UASB performance was observed based on pH, soluble chemical oxygen demand (sCOD) removal efficiency, total volatile fatty acids (VFAs), methane production, composition and yield. A 4 litres UASB was operated under anaerobic conditions using synthetic wastewater for 120 days. The study was carried out in two phases. Phase 1 investigated the performance of UASB during start-up period. Phase 2 investigated the ability of FeCl3 to inhibit SRB in anaerobic treatment of sulphate enriched wastewater at COD/SO4 2- ratios of 5.3, 2.5 and 1.3. Results showed that sCOD removal efficiency during the start-up period was more than 80% and methane production and composition observed were 9 L.day-1 and 67(±2%), respectively. Results of Phase 2 showed that sCOD removal efficiency average values were 78%, 80% and 70%. Methane yield average values were 0.9, 1.2 and 1.3 L CH4.gCODdestroyed -1 when FeCl3 dosage of 10.2, 22.2 and 44.5 mM respectively were used. Scanning electron microscopy (SEM) was used to observe the microbial morphology of anaerobic sludge. The result showed that when UASB was operated at COD/SO4 2- ratio of 1.3, abundant of filamentous rods and long-rod shape bacterium were dominantly attached to the sludge compared to COD/SO4 2- ratio of 2.5. The sludge consisted mainly of rod-shape bacteria which presumably referred to the common shape of SRBs species. However, when UASB was added with FeCl3 at dosage of 22.2 mM and 44.5 mM, the sludge contained no rod-shape bacteria and the morphology of sludge showed the presence of iron sulphide precipitated. The addition of FeCl3 promotes substantially to an even higher methane yield production.